ChemInform Abstract: 1, 8‐Diazabicyclo[5.4.0]undec‐7‐ene (DBU): A Versatile Reagent in Organic Synthesis. Issue 37 (September 2015) - Nand, Bhaskara; Khanna, Garima; Chaudhary, Ankita; Lumb, Anshika; Khurana, Jitender M.
Abstract Review: 122 refs.